LB750. Safety and Immunogenicity of a Bivalent Omicron-Containing Booster Vaccine against COVID-19. (15th December 2022) - Chalkias, Spyros; Harper, Charles; Vrbicky, Keith; Walsh, Stephen R; Essink, Brandon; Brosz, Adam; McGhee, Nichole; Tomassini, Joanne; Chen, Xing; Chang, Ying; Sutherland, Andrea; Montefiori, David; et al.
Abstract: Background: Vaccination strategies that provide enhanced immunity against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants are needed. We evaluated the safety and immunogenicity of a bivalent omicron containing vaccine, mRNA-1273.214 (50 µg), administered as a second booster dose in adult participants. Methods: In this ongoing phase 2/3 trial, 50 µg of the bivalent vaccine mRNA-1273.214 (25 µg each ancestral Wuhan-Hu-1 and omicron BA.1 spike mRNAs) or 50 µg of the authorized mRNA-1273 were administered as second boosters in adults who previously received a 2 dose (100 µg) primary series and a first booster (50 µg) dose of mRNA-1273 (≥ 3 months prior). Primary objectives were safety and reactogenicity and immunogenicity 28 days post-booster dose. Results: In participants with no prior SARS-CoV-2 infection who received booster doses of mRNA-1273.214 (n=334) or mRNA-1273 (n=260), neutralizing antibody (nAb) geometric mean titers (GMTs [95% confidence interval (CI)]) against omicron BA.1 were 2372.4 (2070.6−2718.2) and 1473.5 (1270.8−1708.4), respectively. The model-based GMT ratio (GMR [97.5% CI]) of mRNA-1273.214 compared to mRNA-1273 was 1.75 (1.49−2.04), meeting the pre-specified superiority criterion against omicron BA.1. The pre-specified criterion for non-inferiority against the ancestral SARS-CoV-2 strain was also met. Additionally, mRNA-1273.214 elicited higher GMTs (727.4 [632.8−836.1]) than mRNA-1273 (492.1 [431.1−561.9]) against omicron subvariants BA.4/BA.5 [GMR (95% CI) 1.69 [1.51−1.90])]. Binding antibody responses against alpha, beta, gamma, delta, and omicron were numerically higher in the mRNA-1273.214 group compared to mRNA-1273. mRNA-1273.214 GMTs were consistently higher across age (18-< 65 and ≥ 65 years) and pre-booster SARS-CoV-2 infection subgroups (Figure ). Safety and reactogenicity were similar for both vaccine groups. Conclusion: The bivalent omicron containing mRNA-1273.214 elicited superior nAb responses against omicron 28 days post-immunization compared to mRNA-1273 regardless of age and prior SARS-CoV-2 infection; no new safety concerns were identified. Disclosures: Spyros Chalkias, MD, Moderna, Inc.: Salary|Moderna, Inc.: Stocks/Bonds Stephen R. Walsh, MD, Janssen Vaccines: Grant/Research Support|Moderna, Inc.: Grant/Research Support|NIAID/NIH: Grant/Research Support|Sanofi Pasteur: Grant/Research Support Nichole McGhee, B.S., Moderna, Inc.: Salary|Moderna, Inc.: Stocks/Bonds Joanne Tomassini, Ph.D., Moderna, Inc.: Advisor/Consultant Xing Chen, Sc.D., Moderna, Inc.: Salary|Moderna, Inc.: Stocks/Bonds Ying Chang, M.S., Moderna, Inc.: Salary|Moderna, Inc.: Stocks/Bonds Andrea Sutherland, M.D., MPH, Moderna, Inc.: Salary|Moderna, Inc.: Stocks/Bonds David Montefiori, Ph.D., Moderna, Inc.: Grant/Research Support Bethany Girard, Ph.D., Moderna, Inc.: Salary|Moderna, Inc.: Stocks/Bonds Darin Edwards, Ph.D., Moderna, Inc.: Salary|Moderna, Inc.: Stocks/Bonds Jing Feng, M.S., Moderna, Inc.: Salary|Moderna, Inc.: Stocks/Bonds Honghong Zhou, Ph.D., Moderna, Inc.: Salary|Moderna, Inc.: Stocks/Bonds Lindsey R. Baden, MD, Moderna, Inc.: Grant/Research Support|NIAID: Grant/Research Support Jacqueline Miller, MD, Moderna, Inc.: Salary|Moderna, Inc.: Stocks/Bonds Rituparna Das, M.D., Moderna, Inc.: Salary|Moderna, Inc.: Stocks/Bonds.